Performance analysis for stabilizing the inverted pendulum system using linear quadratic regulator and fuzzy logic controller / Mohamad Syafiq Mohd Arif - Mohd Arif, Mohamad Syafiq (2018)
The inverted pendulum is a system that is not stable and require appropriate controllers to be stable. Inverted pendulum is referred by the researchers in control system engineering field for implementing various control theories. So, in this project the implementation of two controllers, Fuzzy Logic Controller (FLC) and Linear Quadratic Regulator (LQR) are studied to stabilize the inverted pendulum. This study focused on the 2 degree of freedom of inverted pendulum system using simulation of MATLAB Simulink. The development of both controllers are based on the transfer function and state space of inverted pendulum system developed by previous studies. The results of the analysis shows that both controllers could stabilize the inverted pendulum. But, the LQR controllers has the best response and better performance compared to FLC. So, based on this study the LQR controller is more suitable to be implemented with inverted pendulum in order to stabilize it.